Structural econometric approach to bidding in the main refinancing operations of the Eurosystem - Nuno Cassola; Christian Ewerhart; Claudio Morana (European Central Bank (ECB), 2007)
This paper contributes to the existing literature on central bank repoauctions. It is based on a structural econometric approach, whereby the primitives of bidding behavior (individual bid schedules and bid-shading components) are directly estimated. With the estimated parameters we calibrate a theoretical model in order to illustrate some comparative static results. Overall the results suggest that strategic and optimal behavior is prevalent in ECB tenders. We find evidence of a statistically significant bid-shading component, even though the number of bidders is very large. Bid- shading increases with liquidity uncertainty and decreases with the number of participants.
Keywords: G21; G12; D44; E43; E50; 330; monetary policy implementation; primary money; repo auctions; Repo-Geschäft; Refinanzierung; Auktion; Geldpolitik; Zentralbank; Eurozone; EU-Staaten